2003
DOI: 10.1646/02128
|View full text |Cite
|
Sign up to set email alerts
|

Does Müllerian Mimicry Work in Nature? Experiments with Butterflies and Birds (Tyrannidae)1

Abstract: The selective advantage of Miillerian mimicry in nature was investigated by releasing live mimetic and nonmimetic butterflies close to wild, aerial-hunting tropical kingbirds ( Grannw melancholzcus) and cliff-flycatchers (Hirundinea firruginea) in three Amazon habitats (rain forest, a city, and "canga" vegetation). Only mimetic butterflies elicited sight-rejections by birds, but protection conferred by mimicry was restricted to sites in which both predators and mimics co-occurred, as in the case of six mimicry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Experimental field and laboratory studies confirmed the importance of predator learning and experience for recognition of mimetic species (e.g. Chai 1996;Pinheiro 2003;Langham 2006) and brought extensive support for the hypothesis that bird predators are important agents in selection for mimicry and maintenance of spatial colour polymorphism in butterflies (Brower et al 1963;Bullini et al 1969;Coppinger 1970;Mallet & Barton 1989;Kapan 2001;Pinheiro 2003;Langham 2004). Experimental studies also revealed an importance of other traits in addition to coloration (shape and flight pattern) for recognition of the mimetic butterfly species by specialized bird predators (Chai & Srygley 1990;Chai 1996).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Experimental field and laboratory studies confirmed the importance of predator learning and experience for recognition of mimetic species (e.g. Chai 1996;Pinheiro 2003;Langham 2006) and brought extensive support for the hypothesis that bird predators are important agents in selection for mimicry and maintenance of spatial colour polymorphism in butterflies (Brower et al 1963;Bullini et al 1969;Coppinger 1970;Mallet & Barton 1989;Kapan 2001;Pinheiro 2003;Langham 2004). Experimental studies also revealed an importance of other traits in addition to coloration (shape and flight pattern) for recognition of the mimetic butterfly species by specialized bird predators (Chai & Srygley 1990;Chai 1996).…”
Section: Introductionmentioning
confidence: 77%
“…Experimental field and laboratory studies confirmed the importance of predator learning and experience for recognition of mimetic species (e.g. Chai ; Pinheiro ; Langham ) and brought extensive support for the hypothesis that bird predators are important agents in selection for mimicry and maintenance of spatial colour polymorphism in butterflies (Brower et al. ; Bullini et al.…”
Section: Introductionmentioning
confidence: 81%
“…However, behavioural experiments studying the possible effects after consumption, probably involved in the learning of a warning signal as aposematic, might show that minute differences in cyanide concentration are relevant. Short- and long-time effects of chemicals on birds are important to test given that some natural predators have been reported to feed on Heliconius butterflies, such as tropical kingbirds ( Tyrannus melancholicus ) [70]. Furthermore, long-time dose effects of chemicals have been predicted to affect mimicry dynamics by determining the number of attacks needed for predators to learn and avoid a given warning signal [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Both H. erato and H. melpomene are unpalatable and have wing colour patterns that deter potential predators [9], [17], [18]. Across the Americas, each of these two species exhibits approximately 30 warning pattern morphs [3].…”
Section: Introductionmentioning
confidence: 99%